Feasibility study of pyromellitic diimide acceptor for electrochromic applications - Lim, Jovan Jun Long (Nanyang Technological University, 2023)
Polymeric electrochromic (EC) materials are attractive due to their lower cost, vibrant colours, and solution processibility. Potential applications include smart windows, flexible displays, and thermal camouflage. Donor-acceptor (D-A) polymers further expand the possibilities by enabling extensive structural modification to fine-tune polymer properties. In this work, Pyromellitic Diimide (PMDI) was studied as a potential acceptor species in alternating D-A polymers.